Asrooru al-Dilaalah Fi Ba'dhi Abyaati Alfiyah (Diraasah Tahliliyah 'Ala 'Asaasi al-Tarbiyah as-Suluukiyah) - Agung Setiawan (Jurnal Alsinatuna, 2015)
This article describes and interprets the values of character education which are implied in the couplets of Alfiyah Ibnu Malik. The method of data collection used here is documentation. The collected data was analyzed by content analysis. The research result shows that the values of character education implied in the couplets of Alfiyah Ibnu Malik globally divided into three parts, they are character education to Allah and His prophets such as praising Allah and sending salawat to prophet Muhammad, character education to own self such as being honest, and optimistic, and also character education in the household and society such as respecting others.